Global sourcing of complex production processes - Christian Schwarz; Jens Suedekum (Institute for the Study of Labor (IZA), 2010)
We develop a theory of a firm in an environment with incomplete contracts. The firm's headquarter decides on the complexity, the organization, and the global scale of its production process. Specifically, it decides: i) on the mass of symmetric intermediate inputs that are part of the value chain, ii) if the supplier of each component is an external contractor or an integrated affiliate, and iii) if the supplier is offshored to a foreign low-wage country. Afterwards we consider a related scenario where the headquarter contracts with a given number of two asymmetric suppliers. Our model is consistent with several stylized facts from the recent literature that existing theories of multinational firms cannot account for.
Keywords: F12; D23; L23; 330; multinational firms; outsourcing; intra-firm trade; offshoring; vertical FDI